Non-Targeted Analysis Using Gas Chromatography-Mass Spectrometry for Evaluation of Chemical Composition of E-Vapor Products - Shah, Niti H.; Noe, Michael R.; Agnew-Heard, Kimberly A.; Pithawalla, Yezdi B.; Gardner, William P.; Chakraborty, Saibal; McCutcheon, Nicholas; Grisevich, Hannah; Hurst, Thomas J.; Morton, Michael J.; Melvin, Matt S.; Miller IV, John H. (Frontiers in Chemistry, 2021)
The Premarket Tobacco Product Applications (PMTA) guidance issued by the FDA for Electronic Nicotine Delivery Systems (ENDS) recommends that, in addition to reporting Harmful and Potentially Harmful Constituents (HPHCs), manufacturers should evaluate these products for other chemicals that could form during use and over time. Although e-vapor product aerosols are considerably less complex than mainstream smoke from cigarettes and Heated Tobacco Product (HTP) aerosols, there are challenges with performing a comprehensive chemical characterization. Some of these challenges include the complexity of the e-liquid chemical compositions, the variety of flavors used, and the aerosol collection efficiency of volatile and semi-volatile compounds generated from aerosols. In this study, a non-targeted analysis (NTA) method was developed using gas chromatography-mass spectrometry (GC-MS) that allows evaluation of volatile and semi-volatile compounds in e-liquids and aerosols of e-vapor products. The method employed an automated data analysis workflow using Agilent MassHunter Unknowns Analysis software for mass spectral deconvolution, peak detection, and library searching and reporting. The automated process ensured data integrity and consistency of compound identification with >99% of known compounds being identified using an in-house custom mass spectral library. The custom library was created to aid in compound identifications and includes over 1100 unique mass spectral entries, of which 600 have been confirmed from reference standard comparisons. The method validation included: accuracy, precision, repeatability, limit of detection, and selectivity. The validation also demonstrated that this semi-quantitative method provides estimated concentrations with an accuracy ranging between 0.5 to 2.0-fold as compared to the actual values. A limit of detection threshold of 0.7 ppm was established based on instrument sensitivity and accuracy of the compounds identified. To demonstrate the application of this method we share results from the comprehensive chemical profile of e-liquids and aerosols collected from a marketed e-vapor product. Applying the data processing workflow developed here, 46 compounds were detected in the e-liquid formulation and 55 compounds in the aerosol sample. More than 50% of compounds reported have been confirmed with reference standards. The profiling approach described in this publication is applicable to evaluating volatile and semi-volatile compounds in e-vapor products.